Administrative Transformation Toward Integrated Digital Education Services at Madrasah - Muhammad Khoirul Anam; Ichsan Iqbal Firdaus; Yuliang Angga Pratama; Lailis Sofia; Kholi Sotus Sariroh; Naimul Khunaifa (Journal of Educational Management Research, 2026)
This study aims to analyze the digital transformation of educational administration at MTs Miftahul Jannah, Ngawi, in order to improve service quality and operational efficiency. In the digital era, educational institutions are required to shift from manual administrative processes to integrated digital systems to ensure transparency and data-driven decision-making. This research employed a qualitative approach using a field research design. Data were collected through in-depth interviews, focus group discussions (FGDs), and field observations involving the principal, administrative staff, and students. Data analysis followed the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The findings indicate that MTs Miftahul Jannah has successfully initiated digital transformation in financial administration by utilizing digital platforms such as Google Forms and AppSheet, which contributed to improved efficiency, accuracy, and responsiveness of administrative services. However, the transformation has not yet been fully integrated due to challenges related to unstable internet connectivity and limited digital literacy among human resources. The study implies that sustainable digital transformation in madrasah administration requires continuous capacity building, systematic training programs, and strengthened technological infrastructure. These efforts are essential to achieving a fully integrated digital education service system by 2029